Study of Vortices Formation in Lateral Intakes of Pumping Stations - Elgindi, Muhammad (AUC Knowledge Fountain, 2024)
The inefficient design of pumping stations leads to undesirable flow characteristics and the formation of vortices in the sump. These undesirable flow features adversely affect the pumping unit performance and increase the operation and maintenance cost. The aim of this thesis is to assess the ability of the Realizable turbulence model to predict the formation of free-surface and submerged vortices within lateral pumping stations’ intakes. Additionally, the study aims to investigate the effect of the flow ratio and bottom clearance on the flow characteristics and the vortices formation in the sump. Finally, the study introduces an assessment of curtain walls and floor cones as anti-vortex devices in reducing the probability of vortices formation and enhancing the flow behavior in lateral intakes. The results proved the ability of the Realizable turbulence model to capture the complex flow features in the lateral intakes as compared to the experimental results from Anasar & Nakato (2001). Additionally, it was shown that although the design of the intake is in agreement with the requirements of the design codes, it did not prevent the formation of the free surface and floor-attached vortices. Investigating the bottom clearance while maintaining the water depth in the intake sump constant revealed that as the clearance increased, the vorticity magnitude was reported to decrease, even in the cases where the submergence depth above the inlet of the pipe was less than the recommended values. Which suggests that no free surface vortices were forming and extending to the suction pipe. Increasing the flow ratio between the flow in the sump and that in the main channel led to enhancing the flow uniformity in the intake; however, the values of vorticity at the inlet of the bell mouth were found to be increasing. Adding a curtain wall in the sump in general led to reducing the vorticity magnitude at the inlet of the suction pipe and improving the flow uniformity in the sump. However, it was found that locating the curtain wall near the inlet of the sump or near its center increased the vorticity magnitude at the inlet of the suction pipe. On the other hand, when it was located in between these two limits, a global minimum in the vorticity values was reported. Additionally, an enhancement in the flow uniformity was reported by using the curtain wall in the sump. However, the flow characteristics became more complicated, and new vortices were noticed forming in the sump. The reduction in the vorticity magnitude at the inlet of the bell mouth was due to the interaction between the new and old vortices formed in the sump, and the achieved reduction in vorticity was noticed to be not guaranteed. The curtain wall height did not have a significant effect on the area-weighted average vorticity magnitude; however, after a certain limit, the increase in the curtain wall height was reported to increase the maximum vorticity at the inlet of the bell mouth. Similarly, the effect of the height on the flow uniformity was found to be insignificant except for short curtain walls where the velocity uniformity was noticed to drop near the center of the sump. The use of a floor cone in lateral intakes was found to be not recommended as the results showed that adding a floor cone beneath the inlet of the bell-mouth led to increasing the vorticity magnitude at the inlet of the suction pipe and increasing its height had an adverse effect on the vorticity value by increasing it even more. Its effect on the velocity uniformity was noticed to be insignificant as noticed by the minor changes in the uniformity index distribution in the sump. The inefficient design of pumping stations leads to undesirable flow characteristics and the formation of vortices in the sump. These undesirable flow features adversely affect the pumping unit performance and increase the operation and maintenance cost. The aim of this thesis is to assess the ability of the Realizable turbulence model to predict the formation of free-surface and submerged vortices within lateral pumping stations’ intakes. Additionally, the study aims to investigate the effect of the flow ratio and bottom clearance on the flow characteristics and the vortices formation in the sump. Finally, the study introduces an assessment of curtain walls and floor cones as anti-vortex devices in reducing the probability of vortices formation and enhancing the flow behavior in lateral intakes. The results proved the ability of the Realizable turbulence model to capture the complex flow features in the lateral intakes as compared to the experimental results from Anasar & Nakato (2001). Additionally, it was shown that although the design of the intake is in agreement with the requirements of the design codes, it did not prevent the formation of the free surface and floor-attached vortices. Investigating the bottom clearance while maintaining the water depth in the intake sump constant revealed that as the clearance increased, the vorticity magnitude was reported to decrease, even in the cases where the submergence depth above the inlet of the pipe was less than the recommended values. Which suggests that no free surface vortices were forming and extending to the suction pipe. Increasing the flow ratio between the flow in the sump and that in the main channel led to enhancing the flow uniformity in the intake; however, the values of vorticity at the inlet of the bell mouth were found to be increasing. Adding a curtain wall in the sump in general led to reducing the vorticity magnitude at the inlet of the suction pipe and improving the flow uniformity in the sump. However, it was found that locating the curtain wall near the inlet of the sump or near its center increased the vorticity magnitude at the inlet of the suction pipe. On the other hand, when it was located in between these two limits, a global minimum in the vorticity values was reported. Additionally, an enhancement in the flow uniformity was reported by using the curtain wall in the sump. However, the flow characteristics became more complicated, and new vortices were noticed forming in the sump. The reduction in the vorticity magnitude at the inlet of the bell mouth was due to the interaction between the new and old vortices formed in the sump, and the achieved reduction in vorticity was noticed to be not guaranteed. The curtain wall height did not have a significant effect on the area-weighted average vorticity magnitude; however, after a certain limit, the increase in the curtain wall height was reported to increase the maximum vorticity at the inlet of the bell mouth. Similarly, the effect of the height on the flow uniformity was found to be insignificant except for short curtain walls where the velocity uniformity was noticed to drop near the center of the sump. The use of a floor cone in lateral intakes was found to be not recommended as the results showed that adding a floor cone beneath the inlet of the bell-mouth led to increasing the vorticity magnitude at the inlet of the suction pipe and increasing its height had an adverse effect on the vorticity value by increasing it even more. Its effect on the velocity uniformity was noticed to be insignificant as noticed by the minor changes in the uniformity index distribution in the sump.